Heterogeneity in expectations and house price dynamics - Alexander Ludwig; Jochen Mankart; Jorge Quintana; Mirko Wiederholt (Leibniz Institute for Financial Research SAFE, 2024)
Expectations are central for housing decisions and heterogeneity in expectations is a robust feature of survey data. We study the implications of heterogeneity in house price growth expectations for the level of house prices. We feed the joint empirical distributions of income, wealth and expectations into a calibrated heterogeneous agents housing model. We find that eliminating heterogeneity in house price growth expectations would raise average house prices and amplify house price fluctuations thereby reducing the fit of the model. Without heterogeneity, average house prices would be about 11 percent higher and the boom-bust cycle would be about 41 percent larger.
Keywords: D14; D84; D31; E21; E30; G21; R21; 330; Housing; survey expectations; house price cycles; life-cycle model